The East Africa Shift in Textile and Apparel Manufacturing: China-Africa Strategies and AGOA's Influence - Weiyi Wang; Jinghao Lu; Wilmot Allen (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2018)
With rapidly rising labor costs and tightening environmental policy, the global textile and apparel industry is expected to shift its center away from China. In fact, Chinese entrepreneurs have long started looking for opportunities in the African continent in the face of fierce domestic competition. What are the opportunities and challenges facing Chinese investment in the textile and apparel sectors in Africa? How can Africa capitalize on the preferential trade provisions of AGOA to boost these sectors? Drawing from field research and literature review, this policy brief by Weiyi Wang, Jinghao Lu, and Wilmot Allen examines the strategies of leading textile and apparel firms and makes recommendations for supporting more of the value chain shift into East Africa.
Keywords: 330